Internal Limiting Membrane Peeling and Flap Inverting under Air in Large Idiopathic Macular Hole Surgery. (25th September 2021) - Zong, Yuan; Wu, Kaicheng; Yu, Jian; Zhou, Changbo; Jiang, Chunhui
Abstract : Purpose . To evaluate the efficacy of internal limiting membrane (ILM) peeling combined with modified flap inverting under air in the treatment of large idiopathic macular hole (MH). Methods . Eyes with a large idiopathic MH (minimum diameter >550  μ m) were included in this study. The surgical procedure included standard 23-gauge pars plana vitrectomy (PPV), ILM peeling, complete fluid-gas exchange, and ILM flap inversion under air. The patients underwent follow-up exam including optical coherence tomography (OCT) and best-corrected visual acuity (BCVA) measurement. Results . Sixteen eyes from 16 patients were included. Mean MH diameter was 681.43 ± 112.12  μ m. After a mean follow-up time of 6.25 ± 2.65 months, in all cases, the MH was closed, and the ILM flap could be seen at the inner surface of the fovea. U-shaped and V-shaped MH closure was achieved in 11 and 5 cases, respectively. The BCVA improved significantly from 1.49 ± 0.35 logMAR to 0.89 ± 0.35 logMAR (p < 0.05 ), and visual acuity of 20/100 or better was achieved in 8 eyes. Conclusion . ILM flap inverting under air was helpful in improving the functional and anatomic outcomes of vitrectomy for large idiopathic MH.